(untitled) (Orinoquia, 2011)
ABSTRACT: The significantincrease in scientific publications in Colombia during the last fewyears(reaching 372in- dexed journals to date in thenational bibliographicalindex,Publindex)hasled to questioning their true quality. This could have been worse, compared to the number of journals from countries having greater trajectoryand research capacity.Such unusual increase has been attributed to (amongst other factors)thefinancialrecognition paid for publications in universities, institutionalaccreditation orthe result of the market competitionmodel (Delgado, 2011).